2021
DOI: 10.1007/s11227-021-04100-z
|View full text |Cite
|
Sign up to set email alerts
|

Corona virus optimization (CVO): a novel optimization algorithm inspired from the Corona virus pandemic

Abstract: This research introduces a new probabilistic and meta-heuristic optimization approach inspired by the Corona virus pandemic. Corona is an infection that originates from an unknown animal virus, which is of three known types and COVID-19 has been rapidly spreading since late 2019. Based on the SIR model, the virus can easily transmit from one person to several, causing an epidemic over time. Considering the characteristics and behavior of this virus, the current paper presents an optimization algorithm called C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…( 2016 ) 135 Consultant Guide Search (CGS) Wu and Banzhaf ( 2010 ) 136 Co-Operation of Biology Related Algorithm (COBRA) Akhmedova and Semenkin ( 2013 ) 137 Coral Reefs Optimization (CRO) Salcedo-Sanz et al. ( 2014 ) 138 Corona Virus Optimization (CVO) Salehan and Deldari ( 2022 ) 139 Coronavirus Herd Immunity Optimizer (CHIO) Al-Betar et al. ( 2021 ) 140 Coronavirus Optimization Algorithm (COVIDOA) Khalid et al.…”
Section: Metaheuristicsmentioning
confidence: 99%
“…( 2016 ) 135 Consultant Guide Search (CGS) Wu and Banzhaf ( 2010 ) 136 Co-Operation of Biology Related Algorithm (COBRA) Akhmedova and Semenkin ( 2013 ) 137 Coral Reefs Optimization (CRO) Salcedo-Sanz et al. ( 2014 ) 138 Corona Virus Optimization (CVO) Salehan and Deldari ( 2022 ) 139 Coronavirus Herd Immunity Optimizer (CHIO) Al-Betar et al. ( 2021 ) 140 Coronavirus Optimization Algorithm (COVIDOA) Khalid et al.…”
Section: Metaheuristicsmentioning
confidence: 99%
“…The resulting CVO has been used to solve the combinatorial problem of finding the best selection of hyperparameters required for building a DL model in dealing with time series forecasting. In a related study 37 , a variant of CVO is being reported with emphasis on motivating the design of the algorithm based on the SIR model. Selected benchmark functions were used to evaluate the performance of the proposed version of the CVO, so that the problem of discrete and continuous mathematical functions is addressed.…”
Section: Related Workmentioning
confidence: 99%
“…The PSO mechanism has taken inspiration from bird flocking behavior simulation [ 22 ]. It is one of the Swarm Intelligence (SI) nature-inspired sub-domain under biological-based optimization algorithm along with ant colony optimization (ACO) [ 8 ], bacterial foraging optimization (BFO) [ 11 ], grey wolf optimization (GWO) [ 23 ], dragonfly algorithm (DA) [ 24 ], corona virus optimization (CVO) [ 25 ], and others. The PSO is categorized into a stochastic search strategy based on each particle's iterative interaction that forms the swarm.…”
Section: Background On Particle Swarm Optimization (Pso)mentioning
confidence: 99%